Benefits of increasing plant diversity in sustainable agroecosystems. (19th June 2017) - Isbell, Forest; Adler, Paul R.; Eisenhauer, Nico; Fornara, Dario; Kimmel, Kaitlin; Kremen, Claire; Letourneau, Deborah K.; Liebman, Matt; Polley, H. Wayne; Quijas, Sandra; Scherer‐Lorenzen, Michael
Summary: Recent studies have revealed many potential benefits of increasing plant diversity in natural ecosystems, as well as in agroecosystems and production forests. Plant diversity potentially provides a partial to complete substitute for many costly agricultural inputs, such as fertilizers, pesticides, imported pollinators and irrigation. Diversification strategies include enhancing crop genetic diversity, mixed plantings, rotating crops, agroforestry and diversifying landscapes surrounding croplands. Here we briefly review studies considering how increasing plant diversity influences the production of crops, forage, and wood, yield stability, and several regulating and supporting agroecosystem services. We also discuss challenges and recommendations for diversifying agroecosystems. There is consistently strong evidence that strategically increasing plant diversity increases crop and forage yield, wood production, yield stability, pollinators, weed suppression and pest suppression, whereas effects of diversification on soil nutrients and carbon remain poorly understood. Synthesis . The benefits of diversifying agroecosystems are expected to be greatest where the aims are to sustainably intensify production while reducing conventional inputs or to optimize both yields and ecosystem services. Over the next few decades, as monoculture yields continue to decelerate or decline for many crops, and as demand for ecosystem services continues to rise, diversification could become an essential tool for sustaining production and ecosystem services in croplands, rangelands and production forests. Abstract : The benefits of diversifying agroecosystems are expected to be greatest where the aims are to sustainably intensify production while reducing conventional inputs or to optimize both yields and ecosystem services. Over the next few decades, as monoculture yields continue to decelerate or decline for many crops, and as demand for ecosystem services continues to rise, diversification could become an essential tool for sustaining production and ecosystem services in croplands, rangelands and production forests.